Pemanfaatan Isi Rumen Sapi yang Difermentasikan dengan Bakteri Bacillus pumilus terhadap Kandungan Klorofil pada Kultur Dunaliella salina [Use of Content Cow Rumen Fermented With Bacillus pumilus Bacterial Chlorophyll Content On The Culture Dunaliella salina] - Endang Dewi Masithah; Nur Choiriyah; Prayogo Prayogo (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract Dunaliella salina is one type of natural food that can be used in an attempt pembeniha rumen contents of cows is one of the waste obtained from the abattoir which is rich in nutrients. Synthesis of chlorophyll a and b require N and P. The purpose of this study was to determine the effect and the best dose utilization of rumen contents of cows and Bacillus pumilus in the culture of Dunaliella salina in chlorophyll content. The research design used was Completely Randomized Design (CRD) followed by Duncan multiple range test. Treatment research Dunaliella salina was cultured in 500 mL glass bottle with 5 treatments and 4 replications. Culture medium used was sea water that has salinity 30 ppt as much as 0.5 liters of rumen fluid is added 0.5 ml of solution that has been fermented with Bacillus pumilus in accordance with the treatment dose. The results showed that the use of fermenter bacteria Bacillus pumilus in cow rumen contents effect on chlorophyll content and dose fermenter rumen bacterium Bacillus pumilus in cattle that give the best chlorophyll content in Dunaliella salina culture fermentation is the dose intreatment C (7.5 % dose fermentation) reached 0.715653211aí¬molchl/cell on the first day.